Standardisation of Nursery Technique of Tropical Pines II. Germination Medium for Pinus caribaea var. Hondurensis Barr. et. Golf. and P. Patula Schlede & Deppe - Ghosh, R. C.; Singh, R. P.; Sharma, K. K. (Indian Forester, 1974)
no abstract